Assessment of environmental surface contamination with SARS-CoV-2 in concert halls and banquet rooms in Japan. Issue 6 (June 2023) - Matsui, Hidehito; Ueda, Chihiro; Nakajima, Eri; Suzuki, Yumiko; Endo, Harumi; Sugamata, Miho; Takarabe, Yukiko; Yamaguchi, Yukie; Honsho, Masako; Hokari, Rei; Ishiyama, Aki; Imoto, Yasuo; et al.
Abstract: Background: Although crowds are considered to be a risk factor for SARS-CoV-2 transmission, little is known about the changes in environmental surface contamination with the virus when a large number of people attend an event. In this study, we evaluated the changes in environmental surface contamination with SARS-CoV-2. Methods: Environmental samples were collected from concert halls and banquet rooms before and after events in February to April 2022 when the 7-day moving average of new COVID-19 cases in Tokyo was reported to be 5000–18000 cases per day. In total, 632 samples were examined for SARS-CoV-2 by quantitative reverse transcription polymerase chain reaction (RT-qPCR) tests, and RT-qPCR-positive samples were subjected to a plaque assay. Results: The SARS-CoV-2 RNA detection rate before and after the events ranged from 0% to 2.6% versus 0%–5.0% in environmental surface samples, respectively. However, no viable viruses were isolated from all RT-qPCR-positive samples by the plaque assay. There was no significant increase in the environmental surface contamination with SARS-CoV-2 after these events. Conclusions: These findings revealed that indirect contact transmission from environmental fomite does not seem to be of great magnitude in a community setting.